Math

Let's say I have the following:

(a/b) = (c/d)^(k-1)

If I know c, d, and k, then a/b can be calculated easily.
But what if c/d was the unknown, and a/b and k were known?
To find c/d, I was thinking:
ln(a/b) = ln(c/d)^(k-1)
ln(a/b) = (k-1)ln(c/d)
(ln(a/b))/(k-1) = ln(c/d)
e^(ln(a/b))/(k-1) = c/d

Did I do this correctly?

  1. 👍 0
  2. 👎 0
  3. 👁 111
  1. check your last step

    (a/b)^[1 / (k - 1)] = [(c/d)^(k-1)]^[1 / (k - 1)] = c/d

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response